A Road-Holding Index Based on Ride Dynamics for High-Downforce Racing Cars. Issue 1 (May 2019) - Marchesin, Felipe; Barbosa, Roberto Spinola; Gadola, Marco; Chindamo, Daniel
Abstract: This work builds on some of the current industry techniques used in racing to evaluate vertical dynamics performance and propose a new methodology to evaluate vehicle performance. The proposed method creates a quantitative numerical index from the classic tyre vertical load variation frequency response function with some novelties that cover all peculiarities of high downforce race cars. In this method the aerodynamic forces are included as non-linear functions vs ride height and it is shown that they affect system stiffness and damping. As a result, the system response changes as a function of vehicle longitudinal speed. The importance of non-linear suspension rates in this kind of vehicle is also highlighted. The proposed index can also be customized for a certain vehicle speed range. A Formula 3 racecar model has been used as an application example.